PERANCANGAN APLIKASI USER INTERFACE PEMESANAN GEDUNG OLAHRAGA (GORNESIA) - Lintang Aji Yoga Pratama; Sis Churin Ien Aulia; Galih Imam Suwarso (LPPM Unbaja, 2022)
So far, reservations for sports halls have only used unsystematic social media platforms. This raises several problems, one of which the owner of the sports hall may have difficulty in managing his income. This study aims to make it easier for the public to order and system the booking process and payment for the sports hall that will be used. The method used in this study is the SWOT (Strength, Weakness, Opportunity, Threat) method. The expected result of this research is to make it easier for the public to order and system the booking process and payment for the sports hall that will be used.